Enhancing Student’s Writing Ability in Paragraph Writing Through an Outline Strategy at Primary Level - Hassan Ramzan; Muhammad Hafeez (Indonesian Journal Of Educational Research and Review, 2021)
Among language skills, writing is considered the most challenging and complicated skill compared to other skills. The main objective of this research is to analyze the improvement of students' writing skills in writing paragraphs through the outline strategy. The participants in this study were 15 fifth grade students. The participants were selected through random sampling technique. The data obtained were analyzed in percentage. Pre-Test and Post-Test were used as instruments in this study. In the Pre-Test and Post-Test the required items such as writing paragraph titles, grammar, spelling and total sentences (length) of paragraphs are the same. According to the findings, in the Pre-Test the students writing paragraphs were 20.00%, 26.66%, 20.00%, 26.66% (Good), 46.66%, 20.00%, 33.33%, 33 ,33% (Average), 33.33%, 53.33%, 46.66% , 40.00% (Weak) in paragraph headings, use of proper grammar, correct spelling and number of sentences (length ) paragraphs, respectively. After the Pre-Test, the instructor taught the participants about writing paragraphs through an outline strategy for 4 weeks and then conducted a Post-Test. In this test, participants in writing paragraphs through the outline strategy were 46.66%, 53.33%, 60.00%, 53.33% (Good), 40.00%, 26.66%, 33.33%, 40 0.00% (Average), 13.33%, 20.00%, 6.66% , 6.66% (Weak) in paragraph headings, use of proper grammar, correct spelling and number of sentences (length ) paragraphs, respectively. This action-based research shows that the outline strategy can improve students' writing skills.